Increasing Local Content and Economic Growth Based on Research and Technological Innovation: A Bibliometric Analysis - Krisnowo, Agus; ., Subchan; Nasution, Arman Hakim; Permana, Adhi Dharma (Journal of Posthumanism, 2025)
Various countries have implemented local content policies to protect local products. Most of them focus on the use of local labor and natural resources. The aspect of research and innovation as local content has not been widely adopted. This study analyzes research trends, local content and economic growth that intersect with research and innovation through bibliometric analysis. We use the Research Information System for frequency analysis, VOSviewer for data visualization, and Biblioshiny for metrics and citation analysis. We obtained 134 published research articles from the Scopus and Web of Science (WoS) databases, covering the years 2003 to 2023. The results show that the highest number of publications occurred in 2020. The most cited article discussed domestic content and technology intensity. A promising future research topic is the impact of engineering design in increasing local content. It can be developed in the requirements for the auction process.